Skin hypersensitivity tests in buffaloes parasitized with Toxocara vitulorum. - Starke, W. A.; Machado, R. Z.; Bechara, G. H.; Zocoller, M. C. (Elsevier B.V., 1996)
Skin tests were done using larval extract and excretory-secretory (ES) antigens injected intradermally in the neck area of 30, 11- to 200-day-old buffalo calves and nine 27- to 100-day postparturition buffalo cows, the skin of the buffaloes infected with Toxocara vitulorum, mainly calves, demonstrated a hypersensitive response to antigens, especially to the larval extract antigens. Skin hypersensitivity responses were characterized by the presence of dermal nodules with progressive induration and an increase of up to four times the size of the original area at 30 min (immediate type) and at 72 h (delayed type) after injection, Histological preparations of skin reactions at 72 h showed a typical mononuclear cell infiltration, with eosinophils and perivascular cuffing in most of the animals, Fecal examination of 75 animals showed that 65 (86.7%) buffalo calves (9-115 days old) were parasitized with T. vitulorum. The peak of egg output from these animals occurred when they were approximately 45 days old.
Keywords: Toxocara vitulorum; Búfalo; skin hypersensitivity; larval extract; ES antigens